PENGARUH SETTING FISIK TERHADAP PEMANFAATAN RUANG JALAN DI KAWASAN ALUN-ALUN KABUPATEN MALINAU KALIMANTAN UTARA - , Elviana ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The phenomena of space function scramble often occur. They do not only take place in urban areas possessing limited space areas with high number of population and high activity needs but also in urban areas with the availability of wide open spaces, such as Malinau Regency, i.e. on road spaces of The Areas of Malinau Regency Square. The objective of the research was to find the effects of physical setting on the utilization patterns of road space by using rationalistic qualitative approach. The methods of the data collection were (a) the observation of behavior mapping: Place Centered Mapping, Person Centered Mapping and physical track records, (b) semantic differential questionnaires, (c) documentations (d) open and guided interviews. The implementation of the data collection used Time Budget Survey method. The analysis was performed on eight road space fragments with the following findings